Breathe, focus, excel exercises, techniques, and strategies for optimal athletic performance - Martin, Harvey 1989- (Human Kinetics, 2024)
"The author explains breathing's full potential to impact athletic performance and delivers practical, accessible instruction for athletes and those who coach or train them"--Provided by publisher.